Advances in cryptology – EUROCRYPT 2008 27th Annual International Conference on the Theory and Applications of Cryptographic Techniques, Istanbul, Turkey, April 13-17, 2008 : proceedings - EUROCRYPT (Conference) (Lecture notes in computer science ;)
A practical attack on KeeLoq -- Key recovery on hidden monomial multivariate schemes -- Predicting lattice reduction -- Efficient sequential aggregate signed data -- Proving tight security for Rabin-Williams signatures -- Threshold RSA for dynamic and ad-hoc groups -- Towards key-dependent message security in the standard model -- The twin Diffie-Hellman problem and applications -- Predicate encryption supporting disjunctions, polynomial equations, and inner products -- Isogenies and the discrete logarithm problem in Jacobians of genus 3 hyperelliptic curves -- On the indifferentiability of the sponge construction -- A new mode of operation for block ciphers and length-preserving MACs -- Security/efficiency tradeoffs for permutation-based hashing -- New key-recovery attacks on HMAC/NMAC-MD4 and NMAC-MD5 -- Collisions for the LPS expander graph hash function -- Second preimage attacks on dithered hash functions -- Efficient two party and multi party computation against covert adversaries -- Almost-everywhere secure computation -- Truly efficient 2-round perfectly secure message transmission scheme -- Protocols and lower bounds for failure localization in the internet -- HB#: increasing the security and efficiency of HB+ -- Sub-linear zero-knowledge argument for correctness of a shuffle -- Precise concurrent zero knowledge -- Efficient non-interactive proof systems for bilinear groups -- Zero-knowledge sets with short proofs -- Strongly multiplicative ramp schemes from high degree rational points on curves -- Detection of algebraic manipulation with applications to robust secret sharing and fuzzy extractors -- Obfuscating point functions with multibit output -- Isolated proofs of knowledge and isolated zero knowledge -- David and Goliath commitments: UC computation for asymmetric parties using tamper-proof hardware -- New constructions for uc secure computation using tamper-proof hardware.